Dominance hierarchy in different stages of development in colonies of the primitively eusocial wasp Mischocyttarus cerberus styx (Hymenoptera, Vespidae) - Noda, Silvia Cristina Mari; Silva, Eliani Rodrigues da; Giannotti, Edilberto [UNESP] (My University, 2001)
In primitively eusocial insect societies, reproductive division of labor is established by dominance-submission interactions which determine a linear dominance hierarchy. As previously observed for other species, in Mischocyttarus cerberus styx (Hymenoptera, Vespidae), the dominant female is the main egg layer. Most of her attacks were to the females directly beneath in the rank establishing a hierarchy. During the pre-emergence stage, the hierarchy was already defined and in the post-emergence stage, pre-male substage, the frequency of dominance interactions were strong but the hierarchy was still maintained by the first-ranked female. In the decline stage there were many neutral individuals which could be the reproductives of a new colony.